2012
DOI: 10.1186/1755-8794-5-58
|View full text |Cite
|
Sign up to set email alerts
|

A whole blood gene expression-based signature for smoking status

Abstract: BackgroundSmoking is the leading cause of preventable death worldwide and has been shown to increase the risk of multiple diseases including coronary artery disease (CAD). We sought to identify genes whose levels of expression in whole blood correlate with self-reported smoking status.MethodsMicroarrays were used to identify gene expression changes in whole blood which correlated with self-reported smoking status; a set of significant genes from the microarray analysis were validated by qRT-PCR in an independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 23 publications
(35 reference statements)
3
92
0
Order By: Relevance
“…The two strongest enrichments were discovered in two studies that reported the effects of smoking on gene expression and methylation profiles. Fifty genes in the study by Charlesworth et al, 29 15 CpG sites corresponding to 14 unique genes in the study by Wan et al, 30 and five genes in the study by Beineke et al 31 showed significant enrichment against the 7366 unique genes pre-ranked by their absolute t-statistics in our gene set from the combined phenotype analysis using FDR q-values of 0.00058, 0.0012 and 0.0385, respectively.…”
Section: Gsea Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The two strongest enrichments were discovered in two studies that reported the effects of smoking on gene expression and methylation profiles. Fifty genes in the study by Charlesworth et al, 29 15 CpG sites corresponding to 14 unique genes in the study by Wan et al, 30 and five genes in the study by Beineke et al 31 showed significant enrichment against the 7366 unique genes pre-ranked by their absolute t-statistics in our gene set from the combined phenotype analysis using FDR q-values of 0.00058, 0.0012 and 0.0385, respectively.…”
Section: Gsea Resultsmentioning
confidence: 74%
“…In lung tissue, Bossé et al reported up-regulation of FUCA1 among smokers. 32 The study of Beineke et al 31 reported up-regulation of LRRN3, PID1, GPR15 and FUCA1 gene expression in the whole blood of current smokers with LRRN3 being the most statistically significant gene. In a recent study by Guida et al, 33 CpG sites at both LRRN3 and GPR15 were found to be hypomethylated in blood.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the performance of the models based on these six genes in the human samples was only slightly lower than the classification of the human blood samples (correct classification rate BLD-SMK-01 FS ¼ 0.77, QASMC CS ¼ 0.89, QASMC NCS ¼ 0.79; Figure 3 and Table 4). We further retrained a logistic and an LDA model on the same set of genes as Beineke et al 62 While still performing reasonably in cross-validation, the blood signature failed to translate in mice (data not shown).…”
Section: Id3mentioning
confidence: 94%
“…For example, a series of studies using microarray analysis of either unfractionated peripheral blood or purified lymphocytes across the spectrum of tobacco smoke exposure compared with never smokers have identified several genes representing inflammatory pathways that may contribute to CAD. [17][18][19] Those with secondhand smoke exposure could not be distinguished from primary smokers, 17 and neither could recent smokers (quit <2 months previously) be separated from current smokers. 19 However, former smokers (quit >2 months previously) most closely resembled never smokers from the perspective of their gene expression in peripheral blood.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…[17][18][19] Those with secondhand smoke exposure could not be distinguished from primary smokers, 17 and neither could recent smokers (quit <2 months previously) be separated from current smokers. 19 However, former smokers (quit >2 months previously) most closely resembled never smokers from the perspective of their gene expression in peripheral blood. 19 These relationships suggest a dose-response relationship, reinforce the dangers of secondhand smoke exposure, and confirm that smoking cessation is associated with reversible effects on biological pathways that may underlie CAD.…”
Section: Transcriptomicsmentioning
confidence: 99%